Narrated Counter-Narratives and Assumed Grand Narratives about Contemporary Work: Halle Butler’s The New Me - Pignagnoli, Virginia (Narrative Works)

(untitled) (Centre for Digital Scholarship, University of New Brunswick, 2024)
This essay provides an analysis of a post-postmodernist novel, Halle Butler’s The New Me (2019), whose political message is conveyed by the audience’s reconstruction of an authoritative, grand narrative about work as a source of personal fulfilment, which intersects with the main storyline. This authoritative, grand narrative not only informs the narrative communication but also provides the necessary cultural background for Butler’s novel to express its political message—that is, the countering of a normative view about work dynamics in today’s precarious landscape. The audience’s recognition of the interplay of the fictional narrative with a larger one in the background allows the narrative communication to realize its act of “countering.” This essay thus builds on the theory of co-construction (Effron et al., 2019) and counter-narrative approaches (cf. Hyvärinen, 2021, Lueg et al., 2021) to argue that Butler’s novel creates an interplay between the grand narratives about work now—including the “treatment of labour as a calling” and the myth of meritocracy permeating post-recession U.S. society—, and the counter-telling and resisting actions the characters in this narrative do to attend to political change.